Keadilan Distribusi sebagai Capability to Do Good: Integrasi Pendekatan Amartya Sen dengan Konsep Maqāṣid al-Syarī‘ah - Jimmi Saputra; Syukri Iska; Ahmad Lutfi (STIE Amkop Makassar, 2025)
This article aims to formulate a new axiological framework of distributive justice within Islamic Economic Philosophy as a response to the inadequacy of resource-based justice theories. Using a comparative–integrative analytical method grounded in an in-depth literature study of 20 primary sources, this research juxtaposes Amartya Sen’s Capability Approach with the Maqāṣid al-Sharī‘ah paradigm. The analysis reveals that Sen’s concept of capability requires an explicit moral direction, which is fully provided by Maqāṣid through the principle of Falāh, since justice in Islam is inherently tied to ethical and social responsibility. This synthesis results in a conceptual novelty: Distributive Justice as Capability to Do Good (CTDG). CTDG asserts that distribution must generate capabilities that are directed toward doing good (iḥsān) and contributing to society. The concept is practically validated through the instrument of Productive Zakat, where the highest measure of success is the transformation of mustahik into muzakki. This status change demonstrates that the purpose of distribution transcends individual freedom and reaches an ethical-social function that requires empowered individuals to become agents of goodness. CTDG offers a new evaluation standard for Islamic philanthropic institutions, shifting the focus from merely achieving material welfare to developing moral-social capability.